Patient risk factors for pressure ulcer development: Systematic review - Coleman, Susanne; Gorecki, Claudia; Nelson, E. Andrea; Closs, S. José; Defloor, Tom; Halfens, Ruud; Farrin, Amanda; Brown, Julia; Schoonhoven, Lisette; Nixon, Jane (International journal of nursing studies, 2013)
To identify risk factors independently predictive of pressure ulcer development in adult patient populations? A systematic review of primary research was undertaken, based upon methods recommended for effectiveness questions but adapted to identify observational risk factor studies. Fourteen electronic databases were searched, each from inception until March 2010, with hand searching of specialist journals and conference proceedings; contact with experts and a citation search. There was no language restriction. Abstracts were screened, reviewed against the eligibility criteria, data extracted and quality appraised by at least one reviewer and checked by a second. Where necessary, statistical review was undertaken. We developed an assessment framework and quality classification based upon guidelines for assessing quality and methodological considerations in the analysis, meta-analysis and publication of observational studies. Studies were classified as high, moderate, low and very low quality. Risk factors were categorised into risk factor domains and sub-domains. Evidence tables were generated and a summary narrative synthesis by sub-domain and domain was undertaken. Of 5462 abstracts retrieved, 365 were identified as potentially eligible and 54 fulfilled the eligibility criteria. The 54 studies included 34,449 patients and acute and community patient populations. Seventeen studies were classified as high or moderate quality, whilst 37 studies (68.5%) had inadequate numbers of pressure ulcers and other methodological limitations. Risk factors emerging most frequently as independent predictors of pressure ulcer development included three primary domains of mobility/activity, perfusion (including diabetes) and skin/pressure ulcer status. Skin moisture, age, haematological measures, nutrition and general health status are also important, but did not emerge as frequently as the three main domains. Body temperature and immunity may be important but require further confirmatory research. There is limited evidence that either race or gender is important. Overall there is no single factor which can explain pressure ulcer risk, rather a complex interplay of factors which increase the probability of pressure ulcer development. The review highlights the limitations of over-interpretation of results from individual studies and the benefits of reviewing results from a number of studies to develop a more reliable overall assessment of factors which are important in affecting patient susceptibility.